Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
:Table of Content• The Reality of Sustainability of Emerging Cybersecurity Companies in Light of Individuals’ Attitudes in Saudi SocietyEng. Mohammad Abdulaziz Alduriweesh• The Role of Organizational Citizenship Behavior in Improving Job Quality in (School Feeding and Humanitarian Relief Project (SFHRP)Mr. AbdulKarim Dahan Saleh Ali Al-Hawsli, Prof. Abdulkhaleq Hadi Tawwaf• The Effects of Administrative Corruption in Public Office in The Kingdom of Saudi ArabiaMs. Lina Abdullah Alnafisah  , Lecturer \ Bariah Ibrahim Alyahya• The Impact of Job Loyalty on Employee Job Performance: A Case Study of Almarai Company in the Kingdom of Saudi ArabiaDr. Abdulaziz Mosleh Alharbi• Health status as a mediator variable in the case of factors affecting foreign investment in the KSACo-Prof. Vivian Mohammad Nasrulddin, Ms. Salwa Murayziq Alsulami• Employment Contracts for Foreign Workers in the Saudi System - A Legal Study of the Saudi Labor System 2025 AD/1446 AHMr. Maneh Hussein Muhadhal Al-Suqoor• The impact of economic growth on unemployment in Syria during the period (2000-2021)Ms. Loreen Bayan Kshwar
Keywords: The Journal of Economic, Administrative and Legal Sciences